CORRELATION BETWEEN HS-CRP LEVELS AND ERYTHROCYTE SEDIMENTATION RATE VALUES IN PEDIATRIC PATIENTS WITH FEVER - Kusumawardani, Oktaviana Putri Cipta; Cahyani, Anak Agung Ayu Eka; Andini, Ni Komang Sukra (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Fever is the most common disease in children. Fever in children can be found in various conditions such as infection, inflammation, or other unknown causes. One of the laboratory tests that can be used is the hs-CRP and erythrocyte sedimentation rate examination. The purpose of this study was to determine the relationship between hs-CRP levels and erythrocyte sedimentation rate in pediatric febrile patients. The research method was observational with a cross-sectional method using secondary data of 62 samples. Data analysis used the Spearman's rho test. The results of the study showed that most of the pediatric patients who experienced fever were male (59.7%), and the age of the child was 5 years (21%). In pediatric patients with fever, the average hs-CRP level was 19.34 mg/l, and the erythrocyte sedimentation rate was 32.73 mm/hour. The results of the correlation test using the Spearman's rho test method obtained p = 0.001 with r = 0.575, so it can be concluded that there is a moderate and positive relationship between hs-CRP levels and erythrocyte sedimentation rate in pediatric patients with fever.